In vitro and in vivo Characterization of Host–Pathogen Interactions of the L3881 Candida albicans Clinical Isolate - Sucupira, Pedro H. F.; Moura, Tauany R.; Gurgel, Isabella L. S.; Pereira, Tassia T. P.; Padovan, Ana C. B.; Teixeira, Mauro M.; Bahia, Diana; Soriani, Frederico M. (Frontiers in Microbiology, 2022)
Candida albicans is a human commensal fungus and the etiologic agent of infections in immunocompromised individuals. Candida spp. is the most studied human fungal pathogen and the understanding of the mechanisms by which this fungus can evade the immune system affecting immunosuppressed individuals has been extensively studied. Most of these studies focus on different species of Candida and there is much to be understood in variations between strains, specifically different clinical isolates of C. albicans. To understand better the main mechanisms that can be modulated in C. albicans clinical isolates for its virulence ability, we analyzed L3881 strain, that has been previously classified as hypovirulent strain, and SC5314 strain, a virulent wild-type control. Our findings demonstrate that L3881 strain presented higher capacity to evade phagocytosis by macrophages and higher resistance to oxidative stress compared to wild-type. These characteristics was detrimental in generating higher mortality rates for L3881 in animal model of candidiasis, despite this strain been able to induce an upregulation of pro-inflammatory mediators both in vitro and in vivo. These results indicated that in vitro and in vivo functional characterization, more than classical genetic or microbiological factors, are necessary for analysis of virulence in different clinical isolates due to modulation of the host-pathogen interactions.